Design of a Virtual Reality-Based System For Hand and Arm Rehabilitation - Adamovich, S.; Qinyin Qiu; Talati, B.; Fluet, G.; Merians, A. (2007 IEEE 10th International Conference on Rehabilitation Robotics, 2007)
We have previously designed a virtual reality-based training system for hand rehabilitation. Here we report the design of an extended version of the system that allows training of the hemiparetic arm and hand during one training session, and provides haptic assistance during hand motion and during arm movements in three-dimensional space. It also allows bimanual training of the hand and arm. Hand training was based on a virtual piano activity that was designed to promote finger range of motion and independence. Hand exercises included reaching to stationary and moving targets presented in stereo. The use of a three-dimensional robot based on admittance control allowed the use of active force applied by the subject as an input to the haptic controller. Two stroke survivors were trained for three weeks using computer gamelike activities. Subjects improved on movement kinematics and on several of the clinical tests.